2021
DOI: 10.3390/ijerph18062871
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Interannual and Seasonal Links between the Nutrient Regime, Sestonic Chlorophyll and Dominant Bluegreen Algae under the Varying Intensity of Monsoon Precipitation in a Drinking Water Reservoir

Abstract: Long-term variations in reservoir water chemistry could provide essential data in making sustainable water quality management decisions. Here, we analyzed the spatiotemporal variabilities of nutrients, sestonic chlorophyll-a (CHL-a), nutrient enrichment, dominant algal species, and overall chemical water health of the third-largest drinking water reservoir in South Korea during 2000–2020. Our results distinctly explained the strong influence of monsoon rainfall on spatial and annual water chemistry variations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 54 publications
(107 reference statements)
2
22
2
Order By: Relevance
“…The drinking water supply crises tremendously challenge sustainable human society expansion due to global anthropogenic pollution [1][2][3]. Reports abound on the human-caused disturbances at the catchment scale (e.g., by extensive industrialization, urbanization, intensive agriculture) in the lentic ecosystems, resulting in various water quality issues [4][5][6]. One of the most conspicuous and long-term issues is consistent nutrient enrichment (eutrophication), causing significant water quality degradations in the lentic ecosystems [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The drinking water supply crises tremendously challenge sustainable human society expansion due to global anthropogenic pollution [1][2][3]. Reports abound on the human-caused disturbances at the catchment scale (e.g., by extensive industrialization, urbanization, intensive agriculture) in the lentic ecosystems, resulting in various water quality issues [4][5][6]. One of the most conspicuous and long-term issues is consistent nutrient enrichment (eutrophication), causing significant water quality degradations in the lentic ecosystems [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The retention time of each lake can vary according to its hydrologic management. Physical factors of lakes, such as differences in water temperature, upstream river inflow rate, and retention time, significantly affect the delivery and accumulation of thermal energy of water bodies [10,[52][53][54]. Particularly for PD, the average water temperature change in the surface layer and water depth is considered to be complex because mixing occurs inside the lake due to the flow of the Namhan River and the Bukhan River, which have different water temperatures during various periods [55].…”
Section: Stratification Intensity and Its Guiding Factorsmentioning
confidence: 99%
“…The equations used for calculation of TSIs were: As parameters used in Carlson's TSI are to represent algal biomass in water, TSIs of different variables should be identical if biological productivity is limited by p and turbidity of water results from phytoplankton particles. In practice, however, TSIs of different parameters are frequently different from each other, and it was proposed that differences in numerical magnitudes of TSI Chl , TSI TP , and TSI SD can be used to identify different limiting conditions in an aquatic ecosystem [7,41,42]. A simple two-dimensional graphical method in which TSI Chl -TSI SD values are plotted against TSI Chl -TSI TP was proposed for identification of relationships between the trophic state variables [41,43]; this method was utilized in this study.…”
Section: Trophic State Index and Its Deviationmentioning
confidence: 99%
“…The most prominent feature of temporal distributions of the organic parameters was a significant increase toward the end of the study period, with the gradient higher than the first two-thirds. The fact that BOD and COD maintained mostly increasing trends without strong association with precipitation change may indicate that their increases might have been caused by the changes in anthropogenic activities occurring in the surrounding watershed [7,51]. Indeed, a minor increase in industrial pollution sources was reported over the period from 2012 to 2016, with a concurrent decrease in farming activities [52].…”
Section: Inter-annual Variations In Water Quality Parameters and Their Trendsmentioning
confidence: 99%
See 1 more Smart Citation